Understanding the Unique Microenvironment in the Aging Liver - Zhao, Yalei; Yang, Ya; Li, Qian; Li, Jianzhou (Frontiers in Medicine, 2022)
In the past decades, many studies have focused on aging because of our pursuit of longevity. With lifespans extended, the regenerative capacity of the liver gradually declines due to the existence of aging. This is partially due to the unique microenvironment in the aged liver, which affects a series of physiological processes. In this review, we summarize the related researches in the last decade and try to highlight the aging-related alterations in the aged liver.